Exploring the enablers and barriers to social prescribing for people living with long-term neurological conditions: a focus group investigation - Suzanne Simpson; Moira Furlong; Clarissa Giebel (BMC, 2021)
Abstract Background People living with Long Term Neurological Conditions (LTNCs) value peer support and social activities. Psychological support and wellbeing enables them to manage their condition. Social prescribing is a formal process of referring patients to a link worker to co-design a plan to improve their health and wellbeing. Intervention involves supporting participation in activities based within the individual's local community. This study aimed to explore the barriers and enablers to accessing social prescribing for people living with LTNCs (plwLTNCs). Methods A total of four focus groups were carried out with 17 participants, including different neurological conditions such as multiple sclerosis, Fragile X Syndrome, epilepsy, and traumatic brain injury. Two participants were family carers and supported people living with epilepsy and motor neurone disease. Findings were analysed using thematic analysis. Results Five themes were identified: (1) Lack of knowledge; (2) Service provision difficulties; (3) Benefits of social prescribing activities; (4) Physical barriers and (5) Psychological barriers. There was a lack of knowledge about social prescribing and what it actually was. Participants anticipated service provision difficulties relating to funding, link workers need for knowledge of LTNC's and for activities to be varied and individualised. The potential benefits of social prescribing activities were recognised across the groups especially its potential to tackle loneliness and to offer plwLTNC's purpose. Participants highlighted a number of physical barriers such as transport and accessibility; and psychological barriers such as anxiety and stigma. Conclusion Social prescribing aims to address the health inequalities of those living with long-term conditions, however currently it is likely to exclude plwLTNCs. Recommendations for practice and future research are made.